Pre-service English Teachers' Perception on The Challenges and Strategies During Their Teaching Practice Program - Alif , Abdilah Mirza; Hamid, Ade Ismail Ramadhan; Khatimah, Khusnul (English Language Teaching Methodology, 2025)
This study investigates the perceptions of pre-service English teachers regarding the challenges they face and the strategies they employ during their teaching practice. Drawing on semi-structured interviews with five final-year English education students, the research explores real-world classroom experiences from the perspective of those preparing to become full-time teachers. The findings reveal several key challenges, including limited teaching time, inadequate school facilities, classroom management difficulties, low student motivation, and struggles with lesson preparation especially in adapting to unfamiliar content or integrating technology. Despite these obstacles, the participants employed a range of adaptive strategies such as using digital tools (e.g., ChatGPT, Quizizz), aligning materials with student interests, incorporating games and quizzes, and building positive classroom relationships. These approaches reflect a student-centered mindset and highlight the importance of flexibility, creativity, and continuous self-development. The study emphasizes the need for improved teacher preparation programs that support both pedagogical competence and emotional readiness, equipping future educators to thrive in diverse and often unpredictable teaching contexts.